A Surgical Case of Inflammatory Myofibroblastic Tumor of the Liver: Potentially Characteristic Gross Features. (February 2019) - Watanabe, Jiro; Yamada, Sohsuke; Sasaguri, Yasuyuki; Guo, Xin; Kurose, Nozomu; Kitada, Kouji; Inagaki, Masaru; Iwagaki, Hiromi
We herein reported a very rare surgical case of inflammatory myofibroblastic tumor (IMT) of the liver, showing potentially unique and specific gross findings on its cut surface: our IMT demonstrated a relatively well-demarcated and partly infiltrative and likely extrahepatic (ie serosal) but not intrahepatic mass, appearing firm and hemorrhagic, and yellow-whitish in color. The patient, who was a woman in her early 70s with 2-year follow-up for lung cryptococcosis and traffic accident, incidentally presented with unenhanced and low-density, heterogeneous mass on abdominal dynamic CT in the peripheral right lobe of the liver. We could conclusively diagnose the current lesion as the hepatic IMT after thorough analyses including a wide panel of immunohistochemical antibodies. Despite that, all clinicians and pathologists should be aware that the potentially characteristic, extrahepatic gross feature of IMT of the liver might also be one of the powerful supplementary tools for reaching its correct diagnosis. One of our aims in the presented case report is to emphasize that the hepatic IMT should be considered clinicopathologically in the differential diagnosis of mass lesions on the liver.